2004
DOI: 10.1210/jc.2003-031768
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Increases Energy Intake in Cancer Patients with Impaired Appetite: Acute, Randomized, Placebo-Controlled Trial

Abstract: There is a pressing need for more effective appetite-stimulatory therapies for many patient groups including those with cancer. We have previously demonstrated that the gastric hormone ghrelin potently enhances appetite in healthy volunteers. Here, we performed an acute, randomized, placebo-controlled, cross-over clinical trial to determine whether ghrelin stimulates appetite in cancer patients with anorexia. Seven cancer patients who reported loss of appetite were recruited from oncology clinics at Charing Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
254
4
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(280 citation statements)
references
References 24 publications
13
254
4
9
Order By: Relevance
“…Previous ghrelin studies have demonstrated similar increases in energy intake with a lunch-time meal. 2,7 The energy intake on the saline injection day in the current study was relatively high with the men eating more than the women. Despite these high baselines, subcutaneous ghrelin significantly stimulated energy intake.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous ghrelin studies have demonstrated similar increases in energy intake with a lunch-time meal. 2,7 The energy intake on the saline injection day in the current study was relatively high with the men eating more than the women. Despite these high baselines, subcutaneous ghrelin significantly stimulated energy intake.…”
Section: Discussionmentioning
confidence: 63%
“…The starting dose of ghrelin was 0.225 nmol/kg (equivalent to half ghrelin dose administered prior to the meal in our previous intravenous infusion study). 2 Doses were thereafter increased by a factor of two. No side effects were observed or reported at any dose of ghrelin administered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one pilot study, seven cancer patients had 31% higher energy intake with i.v. ghrelin than with placebo (5 pmol kg À1 min À1 for 180 min equals 3 mg kg À1 ), with no adverse effects (Neary et al, 2004).…”
mentioning
confidence: 96%
“…More recenlty, dronabinol and other cannabinoids were proposed to stimulate appetite (Fide et al, 2005), through both a direct action on the endocannabinoid receptors, and an indirect one on anorexigenic cytokines (Klein et al, 2000;Fide et al, 2005). Finally, gastric cell-derived ghrelin was shown to improve appetite and also to interfere with insulin/IGF-1 dependent pathways (see above); of interest, only anorexic cancer patients benefit from ghrelin administration (Neary et al, 2004).…”
Section: Nutritional Interventionsmentioning
confidence: 99%